Mortalidade por causas externas em Cuiabá-MT : análise da qualidade da informação - Pertile, Anayana Cristina (2016)
Globally, in the population of children, adolescents and young people (aged from 0 to 24 years old), the external causes (accidents and violence) are in the first places as a cause of mortality whose events are registered by the Death Declaration (DD), compulsory and universal completion document in case of death. Considering the magnitude of these death causes in this specific population and the importance of completing the DD to its knowledge, and the lack of studies on the issue in Cuiaba, it is essential to know the reality of the information quality of these statements in the municipality. Objective: To analyze the information quality of children, adolescents and young people Death Declarations (0-24 years) who died of external causes in the city of Cuiaba - MT, in 2013. Methodology: This is a descriptive and cross-sectional study, with retrospective data collection. The study population was composed of children, adolescents and young people (0-24 years) who died from external causes in the city of Cuiaba - MT, in 2013. The data source was the DD and the data collection was performed at the Municipal Health Department of Cuiaba - MT. The instrument used for data collection consisted of closed form, with the characterization of victims and deaths, as well as evaluation criteria for information quality: completeness, consistency, and validity. Data were processed and analyzed through Epi Info using simple and bivariate analyzes (Chi-square statistical test, p= or <0.05). A score was used for completeness and validity of data and proportion of inconsistency. The project was approved by the Ethics Committee by the opinion 829,672 of 10/13/2014. Results: We identified 161 DD by external causes at the age of 0-24 years. Concerning the victims profile, most were between 15 and 24 years old (78.2%), predominantly male (82.0%) enrolled from 6th to 9th grade of Elementary School (44.1%), race/mulatto (66.5%). Concerning the information quality, the score rankings Excellent and Bad prevailed both for completeness and for validity. The found inconsistency percentage was low. Problems were identified in the information quality, as more than one type of calligraphy, lack of medical stamp and lack of information about description and circumstances of the event. Conclusion: The importance of training and awareness among professionals who fill the death declarations to improve the information quality about mortality due to external causes in the city is emphasized.